The Analysis of Fatwa DSN-MUI NO. 21/DSN-MUI/X/2001 Concerning Perspectives of Maqashid Sharia - Azyyati, Salwa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Most Muslims in Indonesia in welcoming the future and efforts to estimate the possible consequences in economic life that will be experienced, need to prepare certain funds early on. One of the efforts to meet these funding needs can be tried through sharia insurance, sharia insurance is insurance with the principle of mutual assistance, protecting among participants through the formation of a collection of funds or tabarru funds'. And managed in accordance with sharia principles to face risks. Insurance is a new case that is still being questioned, how is the maqashid sharia or the method of its activities in line with the principles of sharia. Therefore, to meet the needs and respond to citizens' problems, the National Sharia Council considers and requires to stipulate MUI fatwa NO. 21/DSN-MUI/X/2001 concerning insurance that is based on Sharia principles is used as a guideline by the parties who need it. This paper aims to explore a number of thoughts related to insurance according to Maqashid sharia, and insurance principles that are in accordance with sharia and its methodology in the form of analysis, especially in the MUI fatwa NO. 21/DSN-MUI/X/2001. The results, this study found several economic principles in sharia that must be avoided such as usury, gharar, maysir, tajlis, and risywah.